The Effect of Radec’s Learning Model Assisted by Zoom Application on Science Critical Thinking Ability during Covid-19 Pandemic Era - Muhammad Ilham S; Syarifuddin Kune; Rukli Rukli (Indonesian Journal of Primary Education, 2020)
This study aims to determine the effect of the RADEC learning model assisted by the zoom application on students' critical thinking skills in the Covid-19 pandemic era. This type of research is a quasi experimental research design type nonequivalent control group design. The population in this study were all sixth grade students of SD Negeri Sekompleks Kalukuang Makassar City which consisted of 4 schools with a total number of students being 203 and the research sample was 56 students of class VI SDN Kalukuang 1 Makassar with a random sampling technique. Data collection techniques using test techniques, test techniques are used to determine critical thinking skills in the form of 6 item essay questions. The data analysis technique used independent sample t-test analysis. The results of the study based on descriptive analysis show that the average critical thinking skills of the RADEC learning model are 87.14 and the discovery learning learning model reaches 80.21. This means that the RADEC learning model is better than the discopery learning model, while the inferential analysis results show that the RADEC learning model assisted by the zoom cloud meeting application has a significant effect compared to the discovery learning model on critical thinking skills and science learning outcomes of class VI SDN Kalukuang 1 Makassar. . This is based on the independent sample t-test, the Sig (2-tailed) value is 0.000 0.05. This means that the RADEC learning model is better than the discopery learning model, while the inferential analysis results show that the RADEC learning model assisted by the zoom cloud meeting application has a significant effect compared to the discovery learning model on critical thinking skills and science learning outcomes of class VI SDN Kalukuang 1 Makassar. . This is based on the independent sample t-test, the Sig (2-tailed) value is 0.000 0.05. This means that the RADEC learning model is better than the discopery learning model, while the inferential analysis results show that the RADEC learning model assisted by the zoom cloud meeting application has a significant effect compared to the discovery learning model on critical thinking skills and science learning outcomes of class VI SDN Kalukuang 1 Makassar. . This is based on the independent sample t-test, the Sig (2-tailed) value is 0.000 0.05.